Mucocele on the lower lip. A case report - Velásquez Reyes, Víctor (2011)
The aim of presenting the case was to describe clinically the injury, the emotional impact on children and the treatment performed. The mucocele is the most common lip swelling in children, is a fairly common injury seen in the oral cavity, originating from minor salivary glands, can occur in any area of the mouth settle these glands, but nevertheless, many argue that the most common location is the lower lip by nearly 96 %. Being caused by traumatic occurrences such as bites, microtrauma by orthodontic appliances or as a complication of any intervention, specifically we refer to the extravasation mucoceles found mainly in the lower lip of the young patients.